Pharmacogenomics of antibiotic-induced hypersensitivity reactions: current evidence and implications in clinical practice - Biswas, Mohitosh; Murad, Murshadul Alam; Ashik, Md. Ismail Hossain; Ershadian, Maliheh; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2025)
Adverse drug reactions (ADRs) are gradually becoming a concerning health threat worldwide in patients undergoing acute or chronic therapy. Antibiotics are the main drugs that cause immune-mediated ADRs, such as severe cutaneous adverse reactions (SCARs), allergic reactions, and organ-specific diseases, representing a significant threat to patient safety. In this review, we present the current genetic evidence available for antibiotic-related toxicities from a pharmacogenomics (PGx) perspective. We also explore the current state of PGx-based dosing recommendations and the factors limiting their widespread application in routine clinical practice. Through a systematic literature review, this study identified at least 12 antibiotic–gene pairs (amikacin–MT-RNR1, gentamicin–MT-RNR1, kanamycin–MT-RNR1, streptomycin–MT-RNR1, neomycin–MT-RNR1, tobramycin–MT-RNR1, isoniazid–NAT2, dapsone–HLA-B, co-trimoxazole–HLA-B, HLA-C, flucloxacillin–HLA-B, daunorubicin–SLC28A3, and doxorubicin–SLC28A3) with moderate to high Pharmacogenomics Knowledgebase (PharmGKB) evidence levels for toxicity. However, PGx-based dosing guidelines, as recommended by the Clinical Pharmacogenetics Implementation Consortium (CPIC), the Dutch Pharmacogenetics Working Group (DPWG), and the Canadian Pharmacogenomics Network for Drug Safety (CPNDS), are currently available only for the following antibiotic–gene pairs: amikacin, gentamicin, kanamycin, streptomycin, neomycin, and tobramycin–MT-RNR1; flucloxacillin–HLA-B; dapsone–G6PD; nitrofurantoin–G6PD; and daunorubicin and doxorubicin–RARG, SLC28A3, and UGT1A6. Despite the established and growing genetic evidence for toxicity, particularly for Co-trimoxazole-induced SCARs by HLA-B and HLA-C, dapsone-induced SCARs by the HLA-B, and isoniazid-induced liver injury by the NAT2, insufficient approaches are being undertaken to translate these findings into routine clinical practice. The lack of validation of preliminary genetic associations, due to the scarcity of proper follow-up and large-scale replication, remains a key setback for PGx-based implementation of antibiotic therapy in clinical settings. More focused clinical studies, cost-effectiveness analyses, and polygenic risk score development are required to enable the PGx-based clinical use of antibiotics and optimize both safety and effectiveness in achieving precision medicine.